Influence of parents' and caregivers' characteristics on the outcomes of antiretroviral treatment in Ugandan children - Ntambwe Malangu (AOSIS, 2011)
Background: The purpose of this study was to investigate whether there was an association between characteristics of parents and caregivers, and the outcomes of antiretroviral treatment in children younger than 6 years treated at Mildmay Centre in Uganda. Methods: This study was a cross-sectional study based on the review of records. The records of children treated from January 2000 to July 2005 were included in the analysis as part of a larger study. Descriptive and inferential statistics were used in the analysis of data. Results: Of the 179 children, 57.3% were male, 53.4% were 4-5 years, and their median age was 4 years. The majority of children were cared for, in descending order, by their mothers, aunts, grandmothers, and fathers. Whilst 16.0% were orphans of both parents, 56.9% had one of their parents still alive. With regard to outcomes of antiretroviral treatment, it was found that a CD4 count of less than 15% was the most significant predictor of death, when treatment was initiated only at that late stage. When the influence of caregivers' and parents' characteristics on the outcomes of treatment were considered, the only factor that was associated significantly with clinical improvement was the 'father's unknown human immunodeficiency virus (HIV) status'. The data show that when the father was alive, as well as when both parents were alive, the children had a better chance of survival. Conclusion: The nature of the relationship between caregivers and children on antiretroviral treatment, as well as the HIV and living status of their parents seem to have little positive influence on the clinical, immunological, and survival outcomes of the children on treatment. More studies are needed to investigate other characteristics and relationships that may influence the outcomes of treatment.